Catalytic upgradation of vanillyl alcohol as a lignin model compound via oxidation by transitional metal-based mixed oxide catalysts / Subrata Saha - Subrata , Saha (2018)
In recent days, lignin valorization has attracted a great deal of interests to minimize the dependency on under earthed fossil fuels. Lignin is the third abundant source in the earth which can be the source of potential alternative as renewable energy. However, lignin valorization in industrial scale become a great challenge because of the structural complexity of lignin. Extensive researches has been done in this arena using homogeneous and heterogeneous catalysts. And also, adaptation of other strategies such as unconventional reaction media or activation methods were also explored. But, the low yield of products and less economically valuable products obtained in current valorization techniques drives the thrust of this work to develop heterogeneous catalysts to improve the amount of yield to more valuable products. To build a sustainable lignin valorization strategy, many issues such as a stable heterogeneous catalyst with simple and cost effective synthesis protocol, economically friendly process conditions, as well as high amount of yield need to be addressed. In this work, a simple, facile and economically effective solvent evaporation method has been developed to synthesize highly crystalline, mesoporous, and stable mixed oxide catalysts. The catalytic activity of prepared mixed oxide catalysts was tested in liquid phase oxidation of vanillyl alcohol which represent as a model compound of lignin monomeric structure. In the synthesis protocol of mixed oxide catalysts, different loading of metals and different valent cations (Cu2+, Mn3+, Fe3+ Ti4+, Ce4+) were experimented to observe the apparent effect of cation charge on the catalytic activity. In order to establish the correlation of the physico-chemical properties of the mixed oxide catalyst with the catalytic activity, various characterization techniques such as XRD, HRTEM, Raman, XPS, FESEM, SAED, H2-TPR etc. were applied. In addition, to investigate the best suitable and environmentally benign oxidant for oxidation of vanillyl alcohol in terms of catalytic activity such as H2O2 and air was considered in this report. And also, the optimum reaction conditions such as time, pressure, temperature, oxidants concentration were found for liquid phase oxidation of vanillyl alcohol. The highest catalytic activity (94 % conversion with 86 % selectivity to vanillin) was measured for the catalyst in aerobic oxidation prepared by combination of Cu and Ti with ratio Cu/ Ti= 0.5. The other catalysts was in order of Ce-2Ti> Cu-2Zr > Cu-Mn > Fe-2Ti in view of both conversion and selectivity. The catalytic conversion of the catalysts was in order of Cu-2Ti> Cu- 2Zr> Ce-2Ti> Fe-2Ti > Cu-Mn using H2O2 oxidant. In addition, the catalytic activity of prepared mixed oxide catalysts was found to promote the catalytic conversion to a certain extent to transform vanillyl alcohol into selective vanillin product with the presence of base NaOH using H2O2. Moreover, the spent mixed oxide catalysts was examined for stability measurement in there subsequent oxidation reactions of vanillyl alcohol at the obtained suitable reaction parameters for fresh catalysts. It was worth to note that the catalysts was stable with minimum loss of catalytic activity.